2021
DOI: 10.3389/fcell.2020.567358
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate as a Potential Modulator of the Stem Cell Niche in Cornea

Abstract: Chondroitin sulfate (CS) is an important component of the extracellular matrix in multiple biological tissues. In cornea, the CS glycosaminoglycan (GAG) exists in hybrid form, whereby some of the repeating disaccharides are dermatan sulfate (DS). These CS/DS GAGs in cornea, through their presence on the proteoglycans, decorin and biglycan, help control collagen fibrillogenesis and organization. CS also acts as a regulatory ligand for a spectrum of signaling molecules, including morphogens, cytokines, chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…It has been previously reported that cultured hTM cells in the presence of Dex result in an enlargement of cells without change in proliferation. , Interestingly, human corneal keratocytes and corneal epithelial cell proliferation have been shown to be induced by low concentrations of Dex. , For the first week of study, the proliferation of cells on hydrogels containing GAGs, specifically CS, is higher, regardless of the presence or absence of Dex. This is most likely the result of the ability of CS to stimulate cell proliferation, as shown by previous research on TM and other cell types. However, it remains unclear which biological pathway in the TM is impacted by exogenous CS leading to enhanced cell proliferation. After 2 weeks of culture, the presence of Dex did not impact cell proliferation within a hydrogel type except for GelMA/CS ones.…”
Section: Resultsmentioning
confidence: 93%
“…It has been previously reported that cultured hTM cells in the presence of Dex result in an enlargement of cells without change in proliferation. , Interestingly, human corneal keratocytes and corneal epithelial cell proliferation have been shown to be induced by low concentrations of Dex. , For the first week of study, the proliferation of cells on hydrogels containing GAGs, specifically CS, is higher, regardless of the presence or absence of Dex. This is most likely the result of the ability of CS to stimulate cell proliferation, as shown by previous research on TM and other cell types. However, it remains unclear which biological pathway in the TM is impacted by exogenous CS leading to enhanced cell proliferation. After 2 weeks of culture, the presence of Dex did not impact cell proliferation within a hydrogel type except for GelMA/CS ones.…”
Section: Resultsmentioning
confidence: 93%
“…LSCs certainly need to communicate with their own niche to maintain self-renewal (Li et al, 2007), including specific extracellular matrix (ECM), niche cells, and signaling molecules (Ashworth et al, 2021). The ECM not only anchors the basal epithelium but also mediates intercellular communication and provides distinct mechanical properties that influence LSC phenotype, population, and self-renewal (Gesteira et al, 2017;Gouveia et al, 2019;Zheng et al, 2019;Zhu et al, 2020;Ashworth et al, 2021).…”
Section: A Novel Strategy To Optimize Self-renewal and Expansion Of L...mentioning
confidence: 99%
“…LSCs certainly need to communicate with their own niche to maintain self-renewal (Li et al, 2007), including specific extracellular matrix (ECM), niche cells, and signaling molecules (Ashworth et al, 2021). The ECM not only anchors the basal epithelium but also mediates intercellular communication and provides distinct mechanical properties that influence LSC phenotype, population, and self-renewal (Gesteira et al, 2017;Gouveia et al, 2019;Zheng et al, 2019;Zhu et al, 2020;Ashworth et al, 2021). Additionally, cell-cell communication analysis reveals the central role of LSCs and their bidirectional regulation with various niche cells, such as limbal-mesenchymal stem cells, CD45 + cells, PAX6 + cells, and melanocytes (Yazdanpanah et al, 2019;Altshuler et al, 2021;Chen et al, 2021;Polisetti et al, 2021).…”
Section: A Novel Strategy To Optimize Self-renewal and Expansion Of L...mentioning
confidence: 99%
“…Normally, in such cases, the neighbouring healthy endothelial cells spread out and change shape to cover the gaps left by lost cells, this is clinically known as polymegathism. However, a line of evidence has accumulated over recent years indicating that there is a putative population of endothelial progenitor cells (EPCs) that exhibit stem cell-like characteristics (expression of alkaline phosphatase and nestin) present in the peripheral endothelium (Table 4) [38,73,[90][91][92][93][94][95][96][97][98]. [95].…”
Section: The Corneal Stem Cell Nichementioning
confidence: 99%